The association between GP consultations for non-specific physical symptoms in children and parents: a case-control study. - Mujahed Shraim; Milisa Blagojevic-Bucknall; Christian D Mallen; Kate M Dunn (PLoS ONE)
Background Non-specific physical symptoms (NSPS) such as abdominal pain, headache and musculoskeletal pain are widespread in the community, and are common reasons for visiting a general practitioner (GP). Causes of NSPS are multifactorial, but may include parental influences. Objective To investigate associations between GP consultations for NSPS in parents and their children. Methods Matched case-control study using GP consultation data from 12 GP practices in the United Kingdom. Participants were 1328 children who consulted a GP for NSPS in 2009 (cases), 3980 controls who consulted a GP in 2009 but not for NSPS, plus parents of cases and controls (n = 8354). Primary outcome measure child consultation status for NSPS. Results Maternal consultation for NSPS was associated with significantly increased odds of their child consulting for NSPS (odds ratio (OR) 1.51, 95% confidence intervals (CI) 1.33, 1.73); there was no significant association with paternal consultations (OR 0.87, 95% CI 0.71, 1.08). Each additional maternal consultation for NSPS was associated with an increase in the rate ratio for number of consultations for NSPS in the child by 1.03 (95% CI 1.01, 1.05). This overall association was clearest in maternal-child consultations for painful NSPS and for specific bodily systems including gastrointestinal, musculoskeletal and neurologic symptoms. Conclusions Maternal GP consultation for NSPS is associated with increased odds of GP consultations for NSPS in children. This study included a large sample of children and parents and used medical records data which is not subject to recall bias. However, analysis was based on medical records, thus the presence of NSPS not leading to consultations is unknown. Medical practitioners managing children with NSPS need to be aware of this association.